Thrombocytopenia in 737 adult intensive care unit patients: A real-world study of associated factors, drugs, platelet transfusion, and clinical outcome - Man-ka Zhang (SAGE Open Medicine, 2020)
Objective: We aimed to identify and represent factors associated with thrombocytopenia in intensive care unit, especially the pathogens and drugs related to severe and extremely thrombocytopenia. Then, we aim to compare the mortality of platelet transfusion and non-transfusion in patients with different degrees of thrombocytopenia. Methods: We identified all thrombocytopenic patients in intensive care unit by using platelet-specific values and then extracted electronic health records from our Hospital Information System. Data were statistically analyzed with t test, chi-square test, and logistic regression. Results: We found that infections (32.7%) were the most frequent cause associated with thrombocytopenia, followed by sepsis shock (3.93%) and blood loss (2.99%). Meanwhile, antifungals ( p  = 0.002) and bacterial infection ( p  = 0.037) were associated with severe and extremely severe thrombocytopenia. Finally, we found that the mortality of platelet transfusion and non-transfusion in patients was statistically significant for patients with platelet counts between 30 and 49/nL (χ 2  = 9.719, p  = 0.002). Conclusion: Infection and sepsis emerged as two primary factors associated with thrombocytopenia in intensive care unit. Meanwhile, antifungals and bacterial infection were associated with platelet counts less than 49/nL. Finally, platelet transfusion may be associated with reduced mortality in patients with platelet counts between 30 and 49/nL.